Differential Association of Viral Dynamics With Disease Severity Depending on Patients’ Age Group in COVID-19 - Kim, Yuri; Cheon, Shinhyea; Jeong, Hyeongseok; Park, Uni; Ha, Na-Young; Lee, Jooyeon; Sohn, Kyung Mok; Kim, Yeon-Sook; Cho, Nam-Hyuk (Frontiers in Microbiology, 2021)
Despite a clear association of patient’s age with COVID-19 severity, there has been conflicting data on the association of viral load with disease severity. Here, we investigated the association of viral load dynamics with patient’s age and severity of COVID-19 using a set of respiratory specimens longitudinally collected (mean: 4.8 times/patient) from 64 patients with broad distribution of clinical severity and age during acute phase. Higher viral burden was positively associated with inflammatory responses, as assessed by IL-6, C-reactive protein, and lactate dehydrogenase levels in patients’ plasma collected on the same day, primarily in the younger cohort (≤ 59 years old) and in mild cases of all ages, whereas these were barely detectable in elderly patients (≥ 60 years old) with severe disease. In addition, viral load dynamics in elderly patients were not significantly different between mild and severe cases, even though more enhanced inflammation was consistently observed in the elderly group when compared to the younger group during the acute phase of infection. The positive correlation of viral load with disease severity in younger patients may explain the increased therapeutic responsiveness to current antiviral drugs and neutralizing antibody therapies in younger patients compared to elderly patients. More careful intervention against aging-associated inflammation might be required to mitigate severe disease progression and reduce fatality in COVID-19 patients more than 60 years old.